Effectiveness of An Oral Health Care Workshop in Primary School Teachers of Barakahu; A Pilot Study - Qazi, Sheze Haroon; Mumtaz, Rubina; Masoud, Saba; Tassaduq, Rabia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the effectiveness of an oral health care workshop in enhancing the knowledge of primary school teachersStudy design: Quasi-experimental study.Place and Duration of Study: Primary schools of Barakahu, from Feb to Jun 2019.Methodology: This pilot study was carried out among who attended a training workshop on oral health at various primary schools of Barakahu. Training methods included didactic lectures, demonstrations and audio-visual aids. Scores were graded pre and post workshop as poor, fair and good knowledge. Evaluation was done to assess the effectiveness of the training.Results: Out of 40 participants, 78% had good pre-training knowledge as compared to 83% after the training. As our data was not normally distributed therefore, we applied, Wilcoxon signed ranks test to check the change in the questionnaire scores (pre- and post-workshop). Among the 40 participants, 30 had a higher score post-workshop, while 7 had the same score and 3 participants had the lower score (p-value